2015
DOI: 10.1111/all.12675
|View full text |Cite
|
Sign up to set email alerts
|

MPLA shows attenuated pro‐inflammatory properties and diminished capacity to activate mast cells in comparison with LPS

Abstract: Compared to LPS, MPLA induced a qualitatively similar, but less potent pro-inflammatory immune response, but was unable to activate human or mouse MCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
2
30
0
1
Order By: Relevance
“…Most types of native LPS are potent inducers of NLRP3 inflammasome activation and induce a potent pro-inflammatory response. In agreement with our results, Schülke and colleagues showed that, as compared to its parent molecule LPS, MPLA induced a qualitatively similar but significantly less potent pro-inflammatory immune response in in vitro, ex vivo , and in vivo human and mouse test systems22. They further successfully generated a novel fusion protein consisting of MPLA and a model allergen Ovalbumin (MPLA : Ova), and demonstrated that MPLA : Ova can boost Th1, Th2, and Th17 TC-derived cytokine secretion and hence induce both stronger innate and adaptive immune responses compared to the mixture of both components23.…”
Section: Discussionsupporting
confidence: 93%
“…Most types of native LPS are potent inducers of NLRP3 inflammasome activation and induce a potent pro-inflammatory response. In agreement with our results, Schülke and colleagues showed that, as compared to its parent molecule LPS, MPLA induced a qualitatively similar but significantly less potent pro-inflammatory immune response in in vitro, ex vivo , and in vivo human and mouse test systems22. They further successfully generated a novel fusion protein consisting of MPLA and a model allergen Ovalbumin (MPLA : Ova), and demonstrated that MPLA : Ova can boost Th1, Th2, and Th17 TC-derived cytokine secretion and hence induce both stronger innate and adaptive immune responses compared to the mixture of both components23.…”
Section: Discussionsupporting
confidence: 93%
“…Monophosphoryl lipid A (MPLA), a detoxified derivative of lipid A from lipopolysaccharide (LPS), has been approved by FDA and widely used for vaccine studies. Although safer than LPS, its adjuvant activity is also significantly reduced [18]. Therefore, further improvement of its adjuvant effect is still required.…”
Section: Introductionmentioning
confidence: 99%
“…MPLA is a nontoxic TLR4 ligand that is considered as a promising immune stimulator due to its ability to trigger the induction of pro‐inflammatory cytokines . It has been used as an adjuvant in the development of cancer vaccines and malaria vaccines, and in allergen‐specific immunotherapy . In the current study, MPLA was incorporated into EXOs together with TRP2 using the saponin incubation method.…”
mentioning
confidence: 99%